Comparison of Bacterial Load Parameters in Subgingival Plaque during Peri-implantitis and Periodontitis Using the RT-PCR Method - Oksana Nastych; Myroslav Goncharuk-Khomyn; Anatoliy Foros; Alessandro Cavalcanti; Izzet Yavuz; Vladyslav Tsaryk (University of Zagreb. School of Dental Medicine, 2020)
Objective: To estimate the actual parameters of bacterial load in subgingival plaque during periodontitis and peri-implantitis pathologies using the RT-PCR (real-time polymerase chain reaction) method and evaluate their associations with clinical periodontal indicators. Materials and Methods: Five different groups of subjects were selected according to a formulated design of the study: with mild/moderate periodontitis, with severe periodontitis, with peri-implantitis, healthy periodontal group and healthy peri-implant group. Subgingival plaque samples were formed with paper points inserted in the pocket/sulcus area for 30 seconds. A standardized test the "ParodontoScreen" was provided for identification of target opportunistic pathogens (A. actinomycetemcomitans, P. gingivalis, T. forsythia, P. intermedia, T. denticola) by the RT-PCR. Results: Bacterial load parameters demonstrated a significant tendency towards an increase within periodontitis progression and during the presence of peri-implantitis pathology. Each targeted mean bacterial load level was statistically associated with periodontitis or peri-implantitis pathology (p < 0, 05) according to the provided univariate analyses and upon condition that bacterial load parameters of healthy sites were used as reference for equiparation. The highest correlation values were found between periodontal probing depth and bacterial load parameters of A. actinomycetemcomitans (r=0, 37; p < 0, 05) and P. gingivalis (r=0, 28; p < 0, 05); and also between clinical attachment loss and bacterial load values of A. actinomycetemcomitans (r=0, 38; p < 0, 05) and P. gingivalis (r=0, 24; p < 0, 05). Conclusions: Periodontitis and peri-implantitis are associated with the same microbial pathogens even though the distribution pattern of their bacterial load and detection frequency parameters registered with RT-PCR could be distinct and linked to the individual patient-related conditions and the severity stage of pathology.